Iminodiacetic Acid as a Novel Metal‐Binding Pharmacophore for New Delhi Metallo‐β‐lactamase Inhibitor Development. (7th May 2020) - Chen, Allie Y.; Thomas, Caitlyn A.; Thomas, Pei W.; Yang, Kundi; Cheng, Zishuo; Fast, Walter; Crowder, Michael W.; Cohen, Seth M.
Abstract: The fungal natural product aspergillomarasmine A (AMA) has been identified as a noncompetitive inhibitor of New Delhi metallo‐β‐lactamase‐1 (NDM‐1) that inhibits by removing Zn II from the active‐site. The nonselective metal‐chelating properties and difficult synthesis and derivatization of AMA have hindered the development of this scaffold into a potent and selective inhibitor of NDM‐1. Iminodiacetic acid (IDA) has been identified as the metal‐binding pharmacophore (MBP) core of AMA that can be leveraged for inhibitor development. Herein, we report the use of IDA for fragment‐based drug discovery (FBDD) of NDM‐1 inhibitors. IDA (IC50 =120 μM) was developed into inhibitor 23 f (IC50 =8.6 μM, K i =2.6 μM), which formed a ternary complex with NDM‐1, as evidenced by protein thermal‐shift and native‐state electrospray ionization mass spectrometry (ESI‐MS) experiments. Combining mechanistic analysis with inhibitor derivatization, the use of IDA as an alternative AMA scaffold for NDM‐1 inhibitor development is detailed. Abstract : Iminodiacetic acid (IDA) has been identified as lead fragment for New Delhi metallo‐β‐lactamase inhibitor development. Through fragment‐based drug design, synthesis, and mechanistic analysis, 23 f was identified as a potent inhibitor with the potential to convert traditional metal chelators to ones that form ternary complexes. The IDA fragment and inhibitors provide a roadmap for future metallo‐β‐lactamase inhibitor development.